Technological change, inequality and the collapse of the liberal order - Carlos Lastra-Anadón; Manuel Antonio Mu\~niz (Kiel Institute for the World Economy (IfW), 2017)
We are witnessing the start of a deep and prolonged political convulsion. This convulsion is caused by the impact of technological change on how wealth is generated and distributed in our societies. Since the 1970s advanced economies have seen a strong productivity increase and stagnant labor income. We believe this should be described as a major breach of our social contract. It is leading to the stagnation of income of the Middle Class, growing inequality and, ultimately, a radicalization of our politics. Unless the cause of this is properly diagnosed and the underlying drivers addressed head on we are bound to see a worsening of the convulsion. Here the paper analyzes technological change, its key cause and propose a series of bold experiments that countries should undertake in order to develop a new social contract with its citizens. The risk of doing nothing involves a long period of uncertainty and convulsion as well as the likelihood that little is achieved in tackling the underlying problems.
Keywords: J24; J31; D72; 330; automation; workforce polarization; basic income; public venture capital; vocational education